Research Impact and Sustainability in Education: A Conceptual Literature Review - Ricardo Torres; Ana Raquel Simões; Susana Pinto (MDPI AG, 2024)
Research sustainability and research impact are closely related concepts, both referring to the importance of extending research projects' outcomes, changes or benefits beyond their period of implementation. However, the prominence assigned to these two concepts has been provided in an individualized way. This study aims to understand how research sustainability and impact are portrayed and problematized in the literature, in the field of Education, and how they (inter)connect, identifying reference authors and frameworks and describing factors that influence research sustainability and its impact in Education. A conceptual literature review was conducted, and 31 articles were analyzed under the scope of an interpretative paradigm according to the content analysis methodology, using webQDA 3.0 software as support. First, categories were established to identify reference authors and frameworks. Afterward, an inductive codification was carried out, and 15 categories emerged to research sustainability and its impact on Education. This analysis highlights the interconnectedness of both concepts at the conceptualization level and the factors that influence them. The results allow us to identify and discuss action axes, that need more attention in order to assure research sustainability and to evidence research impact in the field of Education.